First iodocyclization reaction of allene-thioureas: an efficient approach to bicyclic beta-lactams - Garud, Dinesh R.; Jadhav, Amol R.; Lahore, Santosh V.; Kahar, Nilesh M.; Joshi, Rohini R.; Joshi, Ramesh A.; Koketsu, Mamoru (Tetrahedron Letters, 2014)
The regioselective iodocyclization reaction of allene-thioureas is described, for the first time, for the synthesis of bicyclic beta-lactams. The substitution at the allenyl part heavily influenced the iodocyclization reaction. The iodocyclization reaction of the unsubstituted allene-thioureas afforded six-membered 3-thia-1-dethiacephems whereas, the substituted allene-thiourea afforded seven-membered thiazepines along with five-membered isopenams. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Allene; beta-Lactams; Iodocyclization; Regioselective; thiourea

Synthesis of 3-Thia-1-dethiacephems via Regioselective Iodocyclization Reaction - Garud, Dinesh R.; Rode, Navnath D.; Bathe, Sagar R.; Ranpise, Vinod S.; Joshi, Ramesh A.; Joshi, Rohini R.; Koketsu, Mamoru (Synthesis-Stuttgart, 2015)
The key N-homopropargylthiourea intermediates, N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides, were prepared by the reaction of a 4-propargylazetidin-2-one with isothiocyanates. Bicyclic -lactams, i.e. 3-thia-1-dethiacephems, were prepared via highly regioselective iodocyclization reaction of N-substituted 2-oxo-4-propargylazetidine-1-carbothioamides with molecular iodine at room temperature in moderate to excellent yields. A variety of functional groups were well tolerated under the reaction conditions.
Keywords: -lactams; 3-thia-1-dethiacephems; Iodocyclization; Regioselective; thiourea